2020
DOI: 10.1101/2020.04.29.068445
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Cytoskeletal Protein Complex is Essential for Division of Intracellular Amastigotes ofLeishmania mexicana

Abstract: Previous studies in Leishmania mexicana have identified the cytoskeletal protein KHARON as being important for both flagellar trafficking of the glucose transporter GT1 and for successful cytokinesis and survival of infectious amastigote forms inside mammalian macrophages. KHARON is located in three distinct regions of the cytoskeleton: the base of the flagellum, the subpellicular microtubules, and the mitotic spindle. To deconvolve the different functions for KHARON, we have identified two partner proteins, K… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Additionally, a putative cyclic nucleotide phosphodiesterase (PDE), LmxM.08_29.2440, was also enriched in the detergent extracted flagellar proteome, and it is predicted to have a single TMD near its C‐terminus. Tagging and localization of this protein confirmed that it is present in the flagellum and is concentrated toward the distal tip in many promastigotes (Kelly et al, 2020b) (Figure 2c). This protein also appears to localize to intracellular vesicles, so whether its biologically relevant activity is exclusively at the flagellum or also elsewhere is currently uncertain.…”
Section: Flagellar Membrane Proteins Implicated In Sensingsupporting
confidence: 56%
“…Additionally, a putative cyclic nucleotide phosphodiesterase (PDE), LmxM.08_29.2440, was also enriched in the detergent extracted flagellar proteome, and it is predicted to have a single TMD near its C‐terminus. Tagging and localization of this protein confirmed that it is present in the flagellum and is concentrated toward the distal tip in many promastigotes (Kelly et al, 2020b) (Figure 2c). This protein also appears to localize to intracellular vesicles, so whether its biologically relevant activity is exclusively at the flagellum or also elsewhere is currently uncertain.…”
Section: Flagellar Membrane Proteins Implicated In Sensingsupporting
confidence: 56%
“…Parasites were washed twice with ice-cold PBS then resuspended in 1 ml cell lysis buffer 55 were exposed to 100 µM biotin for 10 minutes at 37°C, 5% CO 2 . Monolayers were then rinsed three times with cold PBS and incubated with 2 mL of cell lysis buffer (as above).…”
Section: Detection Of Biotinylated Protein Fractions In T Cruzimentioning
confidence: 99%
“…BirA catalyzes the transformation of biotin to a more reactive form, and the resultant biotin cloud reacts with primary amines of proteins in its vicinity, resulting in their covalent biotinylation (Roux et al, 2018). Subcellular compartments that have been targeted by BioID include the nuclear envelope (Kim et al, 2016b), centrosome (Antonicka et al, 2020), nucleus (preprint: Go et al, 2019), cytoplasm (Redwine et al, 2017), Golgi apparatus (Liu et al, 2018), ER (Hoffman et al, 2019), endosome, lysosome, mitochondrial matrix (Antonicka et al, 2020), cell-cell junctions (Fredriksson et al, 2015), and flagella (Kelly et al, 2020), with labeling efficiency limited in the ER (Roux et al, 2018;preprint: Go et al, 2019). Due to slow reaction kinetics, BioID requires labeling for 18-24 h to produce sufficient material for identification by MS, which can lead to off-target labeling and high background, and somewhat Genetic variants, which may occur rarely across individuals with a specific disease, can be used as the basis of PPI networks.…”
Section: Proximity Labelingmentioning
confidence: 99%
“…Understanding the molecular functions of RAS interactors may help develop effective therapeutics. Kennedy et al (2020) investigated how a common KRAS mutation, KRASG13D, affects EGFR signaling in colorectal cancer (CRC) cells by utilizing AP‐MS to compare the network of 95 bait proteins involved in this pathway in WT and KRAS‐mutated cells. Significant differences in PPIs suggest that the majority of rewiring in the EGFR network results from the gain or loss of interacting proteins, linking KRAS activity to a myriad of adaptive network alterations spanning from core interactions throughout the network periphery.…”
Section: Introductionmentioning
confidence: 99%